IGF-1 and ADMA Levels Are Inversely Correlated in Nondiabetic Ankylosing Spondylitis Patients Undergoing Anti-TNF-Alpha Therapy. (27th August 2014) - Genre, Fernanda; López-Mejías, Raquel; Rueda-Gotor, Javier; Miranda-Filloy, José A.; Ubilla, Begoña; Villar-Bonet, Aurelia; Carnero-López, Beatriz; Gómez-Acebo, Inés; Blanco, Ricardo; Pina, Trinitario; González-Juanatey, Carlos; Llorca, Javier; et al.
Abstract : Like rheumatoid arthritis, ankylosing spondylitis (AS) is also an inflammatory disease associated with accelerated atherosclerosis and the presence of metabolic syndrome (MeS) features. AS patients often display osteoporosis as well as new bone formation. Insulin-like growth factor 1 (IGF-1) is a protein involved in both inflammation and bone metabolism. In the present study we assessed whether disease activity, systemic inflammation, MeS features, adipokines, and biomarkers of endothelial activation were associated with IGF-1 and insulin-like growth factor binding protein-3 (IGFBP-3) levels in a series of 30 nondiabetic AS patients without CV disease undergoing TNF-α antagonist-infliximab therapy. All determinations were made in the fasting state, immediately before an infliximab infusion. Although no association of IGF-1 and IGFBP-3 levels with angiopoietin-2 or osteopontin was found, an inverse correlation between IGF-1 levels and asymmetric dimethylarginine (ADMA), an endogenous endothelial nitric oxide synthase inhibitor that impairs nitric oxide production and secretion promoting endothelial dysfunction, was found (r = - 0.397 ; P = 0.04 ). However, no significant association was found between IGF-1 and IGFBP-3 levels and disease activity, systemic inflammation, metabolic syndrome features, or adipokines. In conclusion, in nondiabetic patients with AS undergoing periodic anti-TNF-α therapy, IGF-1 and ADMA are inversely correlated.